WHO public health laboratories webinar series – an online platform to disseminate testing recommendations and best practices during health emergencies - Céline Barnadas; Lisa Stevens; Natacha Milhano; Ana Carolina Barbosa de Lima; Bruce Struminger; Lauren Burke; Sébastien Cognat (Frontiers in Public Health)
Laboratories play a central role in managing public health emergencies. The COVID-19 pandemic imposed unique challenges on global laboratory systems, including testing protocol uncertainties, supply shortages, rapid need for information dissemination, and disruptions to traditional training methods. In response, the WHO established the Public Health Laboratories (PHL) knowledge sharing webinar series whose goals were to respond to the increased demand in up-to-date and reliable information, which WHO is in a unique position to provide. It also aimed to enhance peer-to-peer exchanges across laboratories. This article outlines the PHL webinar series delivery format and presents how the webinar series was received and perceived by participants and how it evolved to support the response to other health emergencies. Contents of the knowledge sharing sessions, as well as attendance, participants’ satisfaction and application of learning were monitored over time using registration forms, satisfaction polls, an annual survey and focus group discussions. From May 2020 to December 2023, 48 sessions attracted 58,688 registrations from 204 countries and territories. Thirty-five sessions featured presentations of WHO guidance, tools or documents and 39 sessions featured country experience sharing. Initially focused on COVID-19, the series became a tool to rapidly disseminate guidance and best practices during new health emergencies and to address cross-cutting topics relevant to the laboratory workforce. Feedback data shows participants found the webinars very useful (86% respondents), reporting knowledge gains in biosafety, quality management, and laboratory practices. The series facilitated knowledge application, with foreseen changes in workplace procedures and training activities (43% respondents). Barriers such as resource limitations, additional training needs, and connectivity issues were frequently identified. Evidence that this knowledge was subsequently applied by participants, such as through changes in workflow, onwards training events and procedural changes further reinforces the efficacy with which the series was able support the laboratory workforce globally in addressing challenges of the COVID-19 pandemic and other health emergencies. The series utilized sessions on cross-cutting topics to run routinely and to keep a high level of engagement with laboratory professionals globally. This enabled it to act as an adaptable tool that was leveraged effectively and quickly during health emergencies for just-in-time learning.